2023
DOI: 10.1007/s11694-023-01804-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of edible chitosan coating containing Salvia rosmarinus essential oil on quality characteristics and shelf life extension of rabbit meat during chilled storage

Abstract: Rabbit meat is one of the most consumed meats throughout the world and is extremely susceptible to spoilage due to its high protein and moisture content. Natural preservatives with antioxidant and antibacterial properties are needed to maintain meat quality and increase its shelf life. This study examined the effect of 1% chitosan (CH), 0.2% rosemary (Salvia rosmarinus) essential oil (REO), and their combination on pH, total volatile basic nitrogen (TVB-N) and thiobarbituric acid (TBA) levels, and the microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…Pathogenic microorganisms in food are the main culprits in food poisoning incidents. The packaging films containing bioactive ingredients can not only isolate microorganisms but also inhibit the growth of microorganisms owing to their antibacterial properties (El Bayomi et al ., 2023). The growth curve of bacteria in chicken breast samples was measured in this study and the results were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic microorganisms in food are the main culprits in food poisoning incidents. The packaging films containing bioactive ingredients can not only isolate microorganisms but also inhibit the growth of microorganisms owing to their antibacterial properties (El Bayomi et al ., 2023). The growth curve of bacteria in chicken breast samples was measured in this study and the results were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As chemical substances, they are sensitive to pH, temperature and oxygen. Additionally, phenolics may potentially affect the physicochemical stability of the complicated food matrix (El Bayomi et al ., 2023). In this context, composite coating technology was a promising method attributed to protecting active ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, chitosan can be defined as an effective strategy to provide meat quality and shelf life by limiting bacteria counts in foods. The mechanism of the antimicrobial property and efficiency of chitosan could be associated with interaction among positive biopolymer molecules and negative charges in cell structure (No et al, 2007;Abdel-Naeem et al, 2021;El Bayoml et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For the count of EBc in the samples examined, the number of colonies formed after 24 h incubation at 37±1°C determined the growth as stated by Harrigan (1998). All results given as reduction % in Tables 2-6 were calculated according to the formula determined by El Bayoml et al (2023).…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Rabbit meat is a popular culinary product and one of the most consumed meats throughout the world. Its use has recently grown in a number of the Middle Eastern countries, notably Egypt [3][4][5]. It is recognized as an excellent source of easily digestible animal protein, polyunsaturated fatty acids (PUFAs), vitamins, and minerals (such as calcium, magnesium, and zinc), while being low in fat, sodium, and cholesterol [6].…”
Section: Introductionmentioning
confidence: 99%